(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2018)
Bengali Hinduism by and large conforms to the orthodox Vedantic variety of that faith, although in response to the cultural impact of the British in the last century there emerged certain modernistic variants (e.g., the Brahmo Samaj, to which some Westernized high-caste elites were drawn). The Shaivite cult, focusing on worship of the god Shiva and his female counterparts, is widespread among the upper castes, while Vaishnavism, involving devotion to the Lord Krishna, is popular among the lower castes. Bengali Muslims belong overwhelmingly to the Sunni division of Islam and generally conform to the Hanafi school of Islamic law. Popular religion in Bengal often displays syncretism, a mixing of both Hindu and Muslim folk beliefs, deities, and practices. Bengal is famous for its wandering religious mendicant folk musicians (e.g., the Bauls, who disdain caste and conventional HinduMuslim religious distinctions in their worship and way of life). In addition to formal worship at Hindu temples and Muslim mosques, popular worship involving religious folk music is widespread, especially at Vaishnavite gatherings (kirtan) and among Muslim followers of several Sufi orders (tarika) present in Bengal. Bengali Muslims are also known for their practice of pirism, the cultic following of Muslim saints or holy men (calledpirs).